APPLICATION OF JIGSAW TYPE OF COOPERATIVE LEARNING MODEL IN IPS LEARNING TO IMPROVE CRITICAL THINKING ABILITY AND STUDENTS' LEARNING ACHIEVEMENT IN CLASS XI TPHP 2 SMK N WONGSOREJO ACADEMIC YEAR 2015/2016 - Amanda Dwiarsianti; Andrew Timothy Umboh; Bagaskara Putra Sulaksono; Derira Tarisa Harahap (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
AbstractThe quality of education in essence cannot be separated from the quality of the learning process in the classroom, while the quality of learning can be seen from the aspect of the process of student learning outcomes. A good learning process will encourage students to always be actively, creatively, and critically involved so that they can achieve maximum achievement and learning outcomes. In addition to the less than optimal learning achievement among class XI Tphp 2 students, they are also very passive in the social studies learning process. This is proven in the social studies learning process in the classroom where the social studies teacher dominates in delivering the material and students tend to accept without being given the opportunity to convey their ideas about the material presented so that in the social studies learning process the criticality of students is almost not too prominent. In addition to the use of monotonous learning methods, students are also less able to think critically in social studies learning, this is also caused by the low interest in students' learning in social studies subjects.Keywords: cooperative model, social studies learning, critical, achievement